2021
DOI: 10.1039/d0cp06502a
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative etching of S-vacancy defective MoS2 monolayer upon reaction with O2

Abstract: The reactions of O2 with S vacancy sites within a MoS2 monolayer were investigated using Density Functional Theory calculations. We considered the following defects: single S vacancy, double S vacancy,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…Previous theoretical studies on oxidation of TMDs have shown that pristine mono-layers remain intact when exposed to O 2 [22,23,24], which is also in line with our experimental observations. However, O 2 molecules can readily adsorb on chalcogen vacancy defects where they can dissociate into oxygen radicals.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Previous theoretical studies on oxidation of TMDs have shown that pristine mono-layers remain intact when exposed to O 2 [22,23,24], which is also in line with our experimental observations. However, O 2 molecules can readily adsorb on chalcogen vacancy defects where they can dissociate into oxygen radicals.…”
Section: Resultssupporting
confidence: 92%
“…It has been shown that such dissociation is an intermediate step for the oxidative etching of MoS 2 , which, however, is associated with relatively high energy barriers and is not feasible at room temperature [23]. In our experiments we introduce oxygen radicals directly due to the splitting of O 2 under the influence of the electron beam.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…57 Accordingly, the transition time from the physisorbed to a nondissociated chemisorbed state at room temperature and 1 atm is ∼20 h. 57 The energy barriers required for chemisorption and their energetic states once chemisorbed are similar for V S and V 2S . 58 These predictions are consistent with our observations, which demonstrate the weak interaction of ambient air with the SV and the metastability of in-vacuum-generated SVs. However, once formed, chemisorbed O at SV is expected to be extremely stable due to a large binding energy of ∼2.4 eV 59 and high desorption energy of oxygen-bonded molecules.…”
Section: Resultsmentioning
confidence: 99%
“…However, once formed, chemisorbed O at SV is expected to be extremely stable due to a large binding energy of ∼2.4 eV 59 and high desorption energy of oxygen-bonded molecules. 58 To overcome the metastability of SVs under ambient conditions and study the impact of oxygen passivation on chemical and electronic properties of MoS 2 , we performed in situ photoemission experiments in the presence of oxygen. In doing so, we leveraged the X-ray-induced ionization of oxygen 30 to generate reactive species capable of overcoming the kinetic barrier to oxygen chemisorption.…”
Section: Resultsmentioning
confidence: 99%